Proteomic profiling of expression of proteasomal subunits from livers of mice treated with diethylnitrosamine. Issue 2 (26th December 2012) - Yuan, Fuqiang; Lu, Jia; You, Pan; Yang, Zengming; Yang, Pengyuan; Ma, Qiling; Tao, Tao; Wu, Fang‐Xiang; Ressom, Habtom; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> The liver plays a central role in transforming and clearing chemicals and is susceptible to the toxicity from these agents. Diethylnitrosamine is metabolized primarily in the liver by cytochrome P‐450 and can cause DNA damage. The 26S proteasome is a large proteolytic complex that degrades ubiquitinated proteins, and regulates many physiological processes. We used proteomics‐based approaches to examine expressional differences of liver proteasomal subunits from diethylnitrosamine‐treated mice. The expression of most proteasomal subunits was observed to be upregulated in the analysis of 2DE and MALDI‐TOF MS/MS. Some of these differentially expressed proteasomal subunits were further confirmed by Western blot, RT‐PCR, and immunohistochemistry. Our results provided useful information on the relationship between the proteasomal complex and related diseases.